Explaining the rise of nonreligion studies': Subfield formation and institutionalization within the sociology of religion - Bullivant, Stephen (Social compass, 2020)
As recently as 2008, a major reference work in the sociology of religion could (correctly) describe the study of atheism, secularity, and nonreligion as meager, fragmentary, and unappreciated'. Only a decade later, this situation has been radically transformed. Not only is there a substantial, ever-growing, and constantly diversifying (methodologically, theoretically, geographically) research literature, but nonreligion studies' now possesses a full academic architecture' of conferences, journals, monograph series, professional communities, and grant successes. Over this period, the study of nonreligion has become increasingly institutionalized as an established subfield of the sociology of religion. This has not simply come about by magic. On the contrary, there are very good sociological reasons i) why, for over a century, nonreligion failed to take off (outside of certain, telling milieux) as an area of sustained sociological interest; and ii) why and how this has - seemingly so rapidly - changed.